Linkages between Integrator, Grower Involvement and Business Performance: An Excerpt from Preliminary Findings - Ahmad Shabudin Bin Ariffin; Hendrik Lamsali; Shahimi Mohtar (International Journal of Supply Chain Management, 2013)
Abstract - The aim of this study is to explain an investigation over the potential relationships between integrator and grower involvement towards business performance in broiler production. The potential role of employees skill levels as moderating variable between the aforementioned independent and the dependant variables are discussed. Broiler supply chain practices and its corresponding performance indicators in the form of broiler farming operations are among the important measures in the dependant variable (business performance). Based on the extensive survey of relevant literature, a research framework is then proposed. The inclusion of integrator involvement (antecedent), the skill levels (moderating variable) and business performance (dependent variable) in the proposed framework is the main contribution of this study. It is expected that this study will be beneficial to broiler industry, relevant policy makers and the growing body of knowledge of supply chain investigation in the livestock businesses. Keywords: supply chain, broiler, supplier involvement, integrator involvement, grower involvement and business performance